INDIVIDUAL BREAST MILK «BANKING»: NEEDS AND MEANS - O. L. Lukoyanova; T. E. Borovik; G. V. Yatsyk; I. A. Belyaeva; V. I. Furtsev (Вопросы современной педиатрии)
Breastfeeding is the most important postnatal factor in metabolic and immunogenic programming of newborns’ health. When it is impossible to breastfeed the baby best efforts should be applied to maintain lactation in mother in order to feed the baby with expressed breast milk. Feeding with frozen expressed breast milk is as good as breastfeeding in its nutritional and biological values. Expressed breast milk (both native and thawed in 3–6 months) is testified to be safe nutrition in its microbiological features for a breastfed child. The article presents recent capabilities to maintain milk production in a nursing mother, sets forth conditions requiring a baby to be breastfed with expressed milk, either partial or exclisive, indicates medical alerts for breastfeeding. Data for safe and effective baby nursing with expressed breast milk is considered. The ways for creation individual breast milk “bank” and rules for storage of frozen milk are indicated. Authors present results of introduction of new technologies for breastfeeding maintenance. The use of up-to-date breast pumps created on the basis of the studies of lactation physiology and mechanisms by which a baby takes the milk from his mother’s breast, helps to improve efficiency of milk expression, simplifies this process a lot making it more comfortable and effective.Key words: newborns, breastfeeding, expressed breast milk, breast pumps, Individual breast milk «banking».